Health information overload among health consumers: A scoping review. Issue 1 (January 2020) - Khaleel, Israa; Wimmer, Barbara C.; Peterson, Gregory M.; Zaidi, Syed Tabish Razi; Roehrer, Erin; Cummings, Elizabeth; Lee, Kenneth
Highlights: Only a small part of the included records focused on health information overload. Cancer was the main topic of studies that focused on health information overload. Predictors of health information overload were determined such as health literacy. Multi or a single-item scale to measure health information overload were identified. Abstract: Objective: To examine and identify the scope of research addressing health information overload in consumers. Methods: In accordance with a published protocol, six electronic databases (PubMed, CINAHL, ERIC, PsycINFO, Embase, and Scopus), reference lists of included articles, and grey literature (Google Advanced Search and WorldCat) were searched. Articles in English were included, without any limit on the date of publication. Results: Of the 69 records included for final analysis, 22 studies specifically examined health information overload, whereas the remainder peripherally discussed the concept alongside other concepts. The 22 studies focused on one or more of the following: 1) ways to measure health information overload (multi-item/single-item scales); 2) predictors of health information overload - these included low education level, health literacy, and socioeconomic status; and 3) interventions to address information overload, such as videotaped consultations or written materials. Cancer information overload was a popular topic amongst studies that focused on information overload. Conclusion: Based on the identified studies, there is a clear need for future studies that investigate health information overload in consumers with chronic medical conditions other than cancer. Practice Implications: This review is the initial step in facilitating future efforts to create health information that do not overload consumers.